Detailed characterization of early HIV-1 replication dynamics in primary human macrophages - Bejarano Acuña, David Alejandro; Börner, Kathleen; Müller, Barbara; Kräusslich, Hans-Georg (Viruses, 2018)
Macrophages are natural target cells of human immunodeficiency virus type 1 (HIV-1). Viral replication appears to be delayed in these cells compared to lymphocytes; however, little is known about the kinetics of early post-entry events. Time-of-addition experiments using several HIV-1 inhibitors and the detection of reverse transcriptase (RT) products with droplet digital PCR (ddPCR) revealed that early replication was delayed in primary human monocyte-derived macrophages of several donors and peaked late after infection. Direct imaging of reverse-transcription and pre-integration complexes (RTC/PIC) by click-labeling of newly synthesized DNA further confirmed our findings and showed a concomitant shift to the nuclear stage over time. Altering the entry pathway enhanced infectivity but did not affect kinetics of viral replication. The addition of viral protein X (Vpx) enhanced productive infection and accelerated completion of reverse transcription and nuclear entry. We propose that sterile alpha motif (SAM) and histidine/aspartate (HD) domain-containing protein 1 (SAMHD1) activity lowering deoxyribonucleotide triphosphate (dNTP) pools is the principal factor delaying early HIV-1 replication in macrophages.